Evaluation of effect of nilotinib in an experimental corneal neovascularization model - Yıldırım, Hakan; Balbaba, Mehmet; Erdağ, Murat; Canleblebici, Mehmet; Dal, Ali; İlhan, Nevin; Kobat, Sabiha Güngör (MediHealth Academy Yayıncılık, 2022)
Aim: This study aims to investigate the neovascularization-inhibiting effect of topical nilotinib and to determine the effective dose of nilotinib. Material and Method: In this study, 42 healthy Wistar albino rats were randomly divided into six groups. The left corneas of all rats except group 1 were cauterized with silver nitrate. Group 1 was the healthy control, with no corneal vascularization, which did not receive any treatment; Group 2 (sham) did not receive treatment, only topical DMSO; Groups 3, 4, and 5 received topical nilotinib at doses of 10, 20, and 40 ?M three times a day, respectively; Group 6 received 5 mg/dL topical bevacizumab three times for a day for seven days. On the 8th day, photographs of the corneas were taken, and the percentage of corneal neovascularization area was calculated. Following all rats being killed via anesthesia, the corneas were removed to determine the levels of vascular endothelial growth factor (VEGF) and platelet-derived growth factor (PDGF) ELISA and corneal immune staining. Results: Other than Group 3, the percentage of neovascular corneal area was lower in the treatment groups compared to Group 2 (p
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi